PENGARUH LIKUIDITAS, SOLVABILITAS, WORKING CAPITAL TURNOVER SERTA PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB-SEKTOR FOOD & STAPLER RETAILING YANG TERDAFTAR PADA BEI PERIODE 2019-2023 - Sundari, Kurniati; Nugraeni, Nugraeni (JURNAL ILMIAH EDUNOMIKA, 2024)
The IDX Industrial categorization (IDX-IC) has replaced the JASICA categorization framework for companies listed on the Indonesia Stock Exchange (IDX) to create consistent categories for investor research. A key change is the inclusion of the Food and Staples Retailing sub-sector within the consumer goods category, which includes businesses offering essential products like food and household items. Despite intense competition and narrow profit margins, this sector holds promise due to ongoing demand driven by population growth and urbanization. Important factors influencing profitability in retail include liquidity, solvency, working capital turnover, and sales growth. This study assesses the impact of these variables on the profitability of businesses operating in the IDX's Retailing of Food and Staples subsector from 2019 to 2023. Findings indicate that liquidity does not significantly impact profitability, while solvency has a negative effect. In contrast, sales growth significantly boosts profitability, highlighting its critical role in enhancing corporate profits.